Biochemical markers of bone collagen type I metabolism - O. V. Zaitseva; S. G. Shandrenko; M. M. Veliky (The Ukrainian Biochemical Journal, 2015)
This review focuses on the analysis of diagnostic value of the major bone remodeling markers, in particular synthesis and degradation markers of collagen type I. These include carboxy- and aminoterminal telopeptide, carboxy- and aminoterminal propeptide of procollagen type I, hydroxyproline, hydroxylysine, pyridinoline and deoxypyridinoline. Their measurement allows evaluating the structural and functional conditions and also the rate of metabolic processes in the bone tissue. The advantages and disadvantages of determination of these markers in the condition of different bone diseases were examined. It is shown that determination of bone collagen type I metabolism markers is the most informative for assessment of bone resorption, formation and turnover.